Epigenome-Wide Association Study of Aggressive Behavior. (28th October 2015) - van Dongen, Jenny; Nivard, Michel G.; Baselmans, Bart M. L.; Zilhão, Nuno R.; Ligthart, Lannie; ,; Heijmans, Bastiaan T.; Bartels, Meike; Boomsma, Dorret I.
Abstract : Aggressive behavior is highly heritable, while environmental influences, particularly early in life, are also important. Epigenetic mechanisms, such as DNA methylation, regulate gene expression throughout development and adulthood, and may mediate genetic and environmental effects on complex traits. We performed an epigenome-wide association study (EWAS) to identify regions in the genome where DNA methylation level is associated with aggressive behavior. Subjects took part in longitudinal survey studies from the Netherlands Twin Register (NTR) and participated in the NTR biobank project between 2004 and 2011 ( N = 2, 029, mean age at blood sampling = 36.4 years, SD = 12.4, females = 69.2%). Aggressive behavior was rated with the ASEBA Adult Self-Report (ASR). DNA methylation was measured in whole blood by the Illumina HM450k array. The association between aggressive behavior and DNA methylation level at 411, 169 autosomal sites was tested. Association analyses in the entire cohort showed top sites at cg01792876 (chr8; 116, 684, 801, nearest gene = TRPS1, p = 7.6 × 10 −7, False discovery rate (FDR) = 0.18) and cg06092953 (chr18; 77, 905, 699, nearest gene = PARD6G-AS1, p = 9.0 ×10 −7, FDR = 0.18). Next, we compared methylation levels in 20 pairs of monozygotic (MZ) twins highly discordant for aggression. Here the top sites were cg21557159 (chr 11; 107, 795, 699, nearest gene = RAB39, p = 5.7 × 10 −6, FDR = 0.99), cg08648367 (chr 19; 51, 925, 472, nearest gene = SIGLEC10, p = 7.6 × 10 −6, FDR = 0.99), and cg14212412 (chr 6; 105, 918, 992, nearest gene = PREP, p = 8.0 × 10 −6, FDR = 0.99). The two top hits based on the entire cohort showed the same direction of effect in discordant MZ pairs (cg01792876, P discordant twins = 0.09 and cg06092953, P discordant twins = 0.24). The other way around, two of the three most significant sites in discordant MZ pairs showed the same direction of effect in the entire cohort (cg08648367, Pentire EWAS = 0.59 and cg14212412, Pentire EWAS = 3.1 × 10 −3 ). Gene ontology analysis highlighted significant enrichment of various central nervous system categories among higher-ranking methylation sites. Higher-ranking methylation sites also showed enrichment for DNase I hypersensitive sites and promoter regions, showing that DNA methylation in peripheral tissues is likely to be associated with aggressive behavior.